Seismic performance of concrete-infilled double steel corrugated-plate walls: Experimental research. (15th July 2020) - Zhu, Jing-Shen; Guo, Yan-Lin; Wang, Meng-Zheng; Yang, Xiao; Pi, Yong-Lin
Highlights: Eight I-shaped CDSCW specimens were investigated experimentally. CDSCW specimens showed different failure modes with various axial compression ratios. All CDSCW specimens possessed stable hysteresis loops. A large axial compression ratio weakens bearing capacity and ductility of CDSCWs. The formulae for estimating the bearing capacity of CDSCW specimens are established. Abstract: The Concrete-infilled Double Steel Corrugated-plate Wall (CDSCW) consists of a corrugated part and two vertical boundary elements. The corrugated part is composed of two steel corrugated plates (SCPs) and infilled concrete, where high-strength bolts connect the two SCPs. The two vertical boundary elements are concrete filled steel tubulars. Obviously, owing to the corrugation configuration of SCPs as well as the positive interactive effect among SCPs, infilled concrete and vertical boundary elements, a CDSCW can attain high axial load-bearing efficiency and good seismic performance. This paper presents the experimental seismic performance of CDSCWs by exerting horizontal cyclic loads under constant axial compressions. Eight specimens were tested, with axial compression ratio, shear span to depth ratio and eccentricity of in-plane compressive load as the main research variables. The experimental results indicated all the specimens subjected to compression-bending failure with failure modes closely related to their axial compression ratios. There was a significant negative correlation between the axial compression ratio and the ductility of CDSCW specimens. In addition, the shear to span depth ratio had an important influence on the ductility of CDSCW specimens. Moreover, the experiment showed that the sectional axial strain distribution of CDSCW specimens conformed to the plane section assumption before reaching their peak load-bearing capacities, and most of the steel fibers except the ones near the neutral axis could be considered as plastic when the CDSCW specimens subjected to in-plane combined compression-bending-shear loads. Based on this, the formulae for estimating the load-bearing capacity of the CDSCW specimens under the combination of constant axial compressions and horizontal cyclic loads are established. The comparison between the formula values and the experimental results proves that the formulae are accurate and conservative. The conclusions of the experimental investigation provide fundamentals for the establishment of CDSCW seismic design method.